(untitled) (Agora for Physical Education and Sport, 2020)
After the systematic analysis of five main works by Aristotle – The Nicomachean Ethics, Rhetoric, Politics, Metaphysics and On the Soul-, I observe a very considerable intellectual appreciation of Aristotle for the sport activity, which is manifested in a) an abundant number of references in Rhetoric, Politics and Nicomachean Ethics, b) the inclusion of the sporting and competitive qualities in the lists of goods that are suitable for man, in Rhetoric, c) the educational and social importance that Aristotle gives to sporting activity, in Politics and d) the creation of a rich epistemology on the science of physical exercise and sport, in The Nicomachean Ethics, Rhetoric, Politics and Metaphysics.